The Connective Tissue Phenotype of Glaucomatous Cupping in the Monkey Eye - Clinical and Research Implications - Yang, Hongli (Prog Retin Eye Res, 2017)
In a series of previous publications we have proposed a framework for conceptualizing the optic nerve head (ONH) as a biomechanical structure. That framework proposes important roles for intraocular pressure (IOP), IOP-related stress and strain, cerebrospinal fluid pressure (CSFp), systemic and ocular determinants of blood flow, inflammation, auto-immunity, genetics, and other non-IOP related risk factors in the physiology of ONH aging and the pathophysiology of glaucomatous damage to the ONH. The present report summarizes 20 years of technique development and study results pertinent to the characterization of ONH connective tissue deformation and remodeling in the unilateral monkey experimental glaucoma (EG) model. In it we propose that the defining pathophysiology of a glaucomatous optic neuropathy involves deformation, remodeling, and mechanical failure of the ONH connective tissues. We view this as an active process, driven by astrocyte, microglial, fibroblast and oligodendrocyte mechanobiology. These cells, and the connective tissue phenomena they propagate, have primary and secondary effects on retinal ganglion cell (RGC) axon and laminar beam and retrolaminar capillary homeostasis that may initially be “protective” but eventually lead to RGC axonal injury, repair and/or cell death. The primary goal of this report is to summarize our 3D histomorphometric and optical coherence tomography (OCT)-based evidence for the early onset and progression of ONH connective tissue deformation and remodeling in monkey EG. A second goal is to explain the importance of including ONH connective tissue processes in characterizing the phenotype of a glaucomatous optic neuropathy in all species. A third goal is to summarize our current efforts to move from ONH morphology to the cell biology of connective tissue remodeling and axonal insult early in the disease. A final goal is to facilitate the translation of our findings and ideas into neuroprotective interventions that target these ONH phenomena for therapeutic effect.